The twins K+ and Na+ in plants - Benito, Begoña; Haro, Rosario; Amtmann, Anna; Cuin, Tracey Ann; Dreyer, Ingo (Journal of plant physiology, 2014)
In the earth's crust and in seawater, K+ and Na+ are by far the most available monovalent inorganic cations. Physico-chemically, K+ and Na+ are very similar, but K+ is widely used by plants whereas Na+ can easily reach toxic levels. Indeed, salinity is one of the major and growing threats to agricultural production. In this article, we outline the fundamental bases for the differences between Na+ and K+. We present the foundation of transporter selectivity and summarize findings on transporters of the HKT type, which are reported to transport Na+ and/or Na+ and K+, and may play a central role in Na+ utilization and detoxification in plants. Based on the structural differences in the hydration shells of K+ and Na+, and by comparison with sodium channels, we present an ad hoc mechanistic model that can account for ion permeation through HKTs.